Workshop Dan Pendampingan Survei Karakter Bagi Guru-Guru SD Inpres Buraen 2 Kupang - Yohanes Hariaman Nada (Jurnal Nasional Pengabdian Masyarakat, 2023)
The National Assessment has been carried out simultaneously in Indonesia, but there are still many who do not fully understand the nature of the AN itself. The lack of socialization means that there are still many teachers who experience difficulties in preparing and implementing AN. The same thing was experienced by teachers at SDI Buraen 2, Kupang Regency, and NTT. The service activity aims to socialize the National Assessment with teachers at SDI Buraen 2, especially about one form of evaluation in the AN, namely the character survey. This activity was carried out in three stages: workshops, mentoring, and evaluation. Based on the evaluation results, it was found that this service activity had provided benefits, including: 1) adding insight and understanding to teachers about AN, especially regarding character surveys. 2) The school succeeded in designing school activities that are useful for instilling the characters in the profiles of Pancasila students. 3) Add to the experience of students in dealing with character surveys. Students begin to get to know the situation in the character survey and the questions in the character survey.